Utilization of Web-Based Madrasah E-Learning For Economic Subject Learning Media - Mufaid, Mufaid; Prajanti, Sucihatiningsih Dian Wisika; Khafid, Muhammad (Journal of Economic Education, 2024)
Student learning outcomes remain an important aspect that serves as a standard for the success of learning in schools. Therefore, it is important to understand student learning outcomes. The purpose of this study is to determine the utilization of Madrasah e-learning as a learning media for the economics subject at the State Islamic Senior High School in Demak and to determine the effectiveness of the utilization of Madrasah e-learning in improving student learning outcomes. This research was a quantitative descriptive study. The population in this study consisted of 403 students from the twelfth grade of State Islamic Senior High School of Demak. The sampling technique used was purposive sampling. The data processed in the study used primary data obtained from observations, questionnaires, and learning outcome data distributed directly to Grade XII students of State Islamic Senior High School of Demak. The data analysis method used was descriptive analysis and the difference test between the experimental class and the control class using the Mann-Whitney U statistical test. The results of this study indicate that madrasah e-learning has been proven effective in increasing student learning outcomes, with the percentage of improvement in the experimental class being higher than that of the control class. Learning through web-based media is more effective in increasing student learning outcomes. A suggestion for future research is to examine the differences in the use of madrasah e-learning between young and senior teachers.